Pengaruh Cas Conversion Cycle , Turnover Asset Ratio Dan Firm’s Growth Sales Terhadap Capital Work Pada PT. Bumi Sarana Utama Di Makassar - Tata, Ulvyana; Rina; Syam, Andi Hendra (STIM-LPI Makassar, 2024)
This research was carried out at PT. Bumu Main Facility with the aim of knowing . (1) To determine the effect of cash conversion cycle, asset turnover ratio and firm's sales growth on capital work; (2) To find out the factors that have the most dominant influence on Capital Work at PT. Bumi Main FacilityThe results of the research show that the cycle of changes in cash, total assets and the company's sales growth rate simultaneously have a significant effect on PT's working capital. Bumi Sarana Utama in Makassar. Meanwhile, partially, the cash conversion cycle and total assets have a positive and significant effect on the company's working capital. Meanwhile, the sales growth variable has a negative and insignificant effect on the company's working capital.